Witches, Monsters, and Questions of Nation: Humans and Non-Humans in Akata Witch and Trail of Lightning - Deborah Williams (International Journal of Young Adult Literature, 2020)
Two very different YA novels – one set in Nigeria, the other on a Navajo (Dineh) reservation in the United States – present similarly paradoxical answers to the question about what it means to be human. Both Akata Witch (2011), by Nnedi Okorafor, and Trail of Lightning (2018), by Rebecca Roanhorse suggest that in a world reeling from the impact of the Anthropocene, humanity must learn to see itself as a node in a network, rather than as the apex of a pyramid in which everything below it becomes merely a consumable resource. ‘Human’ in these novels, is no longer a category that automatically denotes superiority. Many scholarly considerations of the post- or trans-human in YA fiction concentrate on how technology has altered human society; the novels I discuss here, however, are more concerned with relationships between the human body and the natural world – or whatever is left of the natural world in the aftermath of the destruction caused by climate change. The heroines of these novels move between the human and the spirit worlds – abilities that cause each of them to be seen as a monster or a freak – and this fluidity becomes an example, I argue, of both the power of female agency and the need to reconceptualize our understandings of human society. Through a consideration of these novels, the article also intervenes in the ongoing critical conversation about cosmopolitanism, which I argue is a practice and not a static principle. I suggest that these novels ask us to conceive of a cosmopolitanism that is not solely about our obligation to humanity (over a nation or a tribe) but rather about our obligations to the globe (of which humanity is but a part).